2019
DOI: 10.1037/cbs0000148
|View full text |Cite
|
Sign up to set email alerts
|

Is collectivistic forgiveness different from individualistic forgiveness? Dispositional correlates of trait forgivingness in Canada and Japan.

Abstract: Trait forgivingness is associated with subjective well-being and positive health outcomes. However, researchers have argued recently that in collectivistic cultures, forgiveness is primarily determined by cultural norms that value social harmony and the forgivers' dispositions are less important than in individualistic cultures. The present study tested whether 18 dispositional variables, such as Big Five personality traits, would be more strongly correlated with trait forgivingness in Canada (an individualist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In addition, the effect of gender was puzzling. Gender tended not to be significantly correlated with forgiveness and apology (when it was, the correlations were weak) in previous studies (e.g., Ohtsubo et al, 2019;Smith et al, 2020). Study 1 corroborated these previous findings: Gender was not associated with either apologetic behavior or forgiveness, regardless of whether the entire sample or subsamples were analyzed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, the effect of gender was puzzling. Gender tended not to be significantly correlated with forgiveness and apology (when it was, the correlations were weak) in previous studies (e.g., Ohtsubo et al, 2019;Smith et al, 2020). Study 1 corroborated these previous findings: Gender was not associated with either apologetic behavior or forgiveness, regardless of whether the entire sample or subsamples were analyzed.…”
Section: Discussionsupporting
confidence: 82%
“…An intriguing question whether the reported pattern is unique to the Japanese sample. Although some scholars have pointed out possible cultural differences in conciliatory tendencies (e.g., Hook et al, 2009 ), there are studies reporting cross-cultural consistency (e.g., Ohtsubo et al, 2012 , 2019 ; Smith et al, 2020 ). If the dominance strategy is flexible (as we discussed above), it is reasonable to expect that the behavioral manifestation of the dominance strategy is more malleable due to the influence of cultural norms.…”
Section: Discussionmentioning
confidence: 99%
“…As for trust and caution, Ohtsubo et al (2019) found that these variables were correlated with trait forgivingness at the interpersonal level. In the intergroup reconciliation context, trust in the other group is considered an important moderator variable of the effect of apologies on forgiveness (e.g., Hornsey & Wohl, 2013; Nadler & Liviatan, 2006).…”
mentioning
confidence: 99%